The Wilms Tumor Gene wt1a Contributes to Blood-Cerebrospinal Fluid Barrier Function in Zebrafish - Hopfenmüller, Vera L.; Perner, Birgit; Reuter, Hanna; Bates, Thomas J. D.; Große, Andreas; Englert, Christoph (Frontiers in Cell and Developmental Biology, 2022)
The Wilms tumor suppressor gene Wt1 encodes a zinc finger transcription factor, which is highly conserved among vertebrates. It is a key regulator of urogenital development and homeostasis but also plays a role in other organs including the spleen and the heart. More recently additional functions for Wt1 in the mammalian central nervous system have been described. In contrast to mammals, bony fish possess two paralogous Wt1 genes, namely wt1a and wt1b. By performing detailed in situ hybridization analyses during zebrafish development, we discovered new expression domains for wt1a in the dorsal hindbrain, the caudal medulla and the spinal cord. Marker analysis identified wt1a expressing cells of the dorsal hindbrain as ependymal cells of the choroid plexus in the myelencephalic ventricle. The choroid plexus acts as a blood-cerebrospinal fluid barrier and thus is crucial for brain homeostasis. By employing wt1a mutant larvae and a dye accumulation assay with fluorescent tracers we demonstrate that Wt1a is required for proper choroid plexus formation and function. Thus, Wt1a contributes to the barrier properties of the choroid plexus in zebrafish, revealing an unexpected role for Wt1 in the zebrafish brain.